2020
DOI: 10.1136/bmjopen-2020-038302
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of occlusion length in recanalized chronic total occlusion lesion: a retrospective cohort study with 5-year follow-up

Abstract: ObjectivesThis study sought to investigate the relationship between occlusion length and long-term outcomes of patients with recanalised chronic total occlusion (CTO) lesion.DesignA retrospective cohort study.SettingFuwai Hospital, National Center for Cardiovascular Disease, Beijing, ChinaParticipantsConsecutive patients with successfully recanalised CTO were included from January 2010 to December 2013.Primary and secondary outcome measuresThe primary endpoint of the present study was a composite event of all-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The first study did not find significant differences in long‐term mortality and MACE, between patients with long and short CTOs, but target vessel revascularization (TVR) was more often performed in patients with lesions ≥30 mm (OR: 4.24; 95% CI: 1.52, 11.84) 21 . The second study demonstrated no difference in long‐term mortality and MACE risk in patients with lesions ≥15 mm, but higher risk of both TVR (hazard ratio (HR): 1.48; 95% CI: 1.01, 2.15) and target lesion revascularization (TLR) (HR: 1.54; 95% CI: 1.03, 2.29) in multivariable analysis 22 …”
Section: Discussionmentioning
confidence: 94%
“…The first study did not find significant differences in long‐term mortality and MACE, between patients with long and short CTOs, but target vessel revascularization (TVR) was more often performed in patients with lesions ≥30 mm (OR: 4.24; 95% CI: 1.52, 11.84) 21 . The second study demonstrated no difference in long‐term mortality and MACE risk in patients with lesions ≥15 mm, but higher risk of both TVR (hazard ratio (HR): 1.48; 95% CI: 1.01, 2.15) and target lesion revascularization (TLR) (HR: 1.54; 95% CI: 1.03, 2.29) in multivariable analysis 22 …”
Section: Discussionmentioning
confidence: 94%
“…In a retrospective analysis by Tian et al, 5-year outcomes demonstrated CTO length >15 mm to be a predictor of TLR, whereas Ahn et al found CTO length >30 mm was associated with higher repeat PCI driven by TVR at 2 years. 38,39 In the diabetic cohort of the OPEN-CTO study, approximately 60% had occlusion length >20 mm, whereas in the dissection and re-entry technique (DART) cohort of the CONSISTENT-CTO study, a mean (± SD) lesion length of 32 ± 22 mm was associated with an overall 2-year TVR of 14.9%, reiterating the potential for ISR and, further, development of downstream in-stent CTO. 13,40 CTO location at the aorto-ostium or bifurcation increases procedural difficulty and carries a higher risk of SF.…”
Section: Lesion-related Factorsmentioning
confidence: 99%
“…While collaterals regress following restoration of antegrade flow, in the event of reocclusion of the recanalized vessel, there is evidence these collaterals can recover to mitigate myocardial ischaemia and reduce allcause death. 10,29,30 Such physiological processes would not be expected to be influenced by treated segment length but whether this accounts for similar short and longer-term survival among our treatment groups remains to be determined.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of 1987 patients who underwent CTO PCI in China from 2010 to 2013, the risk of all-cause death (5.7% vs. 5.1%, p = 0.56) and MI (7.6% vs. 5.9%, p = 0.13) were similar at follow up of 5 years between CTO PCI for long (> 15 mm, n = 1030) and short lesions (length < 15 mm, n = 957). 10 In a single center study of 235 consecutive patients who underwent successful CTO PCI, the incidence of in-hospital complications was found to be similar between short (< 30 mm) and long (≥ 30 mm) CTO lesion lengths. 11 Finally, in a single center study of 102 patients, longer total stent length was found to be independently associated with restenosis (hazard ratio 1.02, CI: 1.00-1.03, p = 0.05).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation